Portrait photograph of an unidentified child, likely male (Cambridgeport, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Charles H. Danforth (photographer):::Photographer:::::::::::: (Cambridgeport, MA; United States; Charles H. Danforth, 2023)
Portrait photograph of an unidentified child, likely male (undated) by Charles H. Danforth, Cambridgeport, MA, from the personal collection of Alexander Wheelock Thayer.